Konsep Pengembangan Ekonomi Penunjang Business Plan Berbasis Perikanan Desa Karangsong Kecamatan Indramayu Kabupaten Indramayu Provinsi Jawa Barat - Rinaldi Agusta Fahlevie; Bernadete Nurmawati; Erita Oktasari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Community-based economic activities are one of the strategic programs to achieve economic growth through the development of the fisheries sector to increase small-scale fisheries businesses (Zamzami & Dwi Hastuti.2019). Indonesia as an archipelagic country has a large potential for fish resources (6,520,100 tons/year), as stated in the Decree of the Minister of Marine Affairs and Fisheries number KEP.45/MEN/2011 concerning the potential of Indonesia's marine resources. The government makes efforts through infrastructure activities that are very important (Rahmayanti, 2018), regional scale and environmental scale with the concept of infrastructure development that supports livelihood activities, the ultimate goal of which is to provide a direct impact on the improvement/development of superior products. Research method uses qualitative descriptive analysis by analyzing data and work programs compiled in a business plan and develop concepts and collect facts. Data collection through documentation that has been obtained both primary and secondary data. Data collection to identify potential fishery-based businesses in Karangsong Village is carried out through the following stages: (1) Surveys are carried out to obtain information and reveal descriptions of identification of needs for supporting fishery-based business plans and management problems of marine product processing; (2) Direct observation is carried out to reveal and obtain a complete and systematic picture of the situation and description of the business of processed marine products; (3) Documentation is carried out to obtain data and information in the form of books, archives, documents, written numbers and pictures in the form of reports and information that can support research.